The role of agriculture and food processing in the chilean economy: results from an input-output analysis - Holland, David; Figueroa, Eugenio; Gilbert, John (Estudios de Economía, 2016)
Chilean agricultural and food processing industries have experienced considerable investment in recent years and are an important part of the export base in Chile. In this paper we use an Input-Output (IO) analysis to review the relative importance of agriculture and food processing to Chile’s economy. We also use the input-output table to examine fifty different sectors contribution to Chilean gross domestic product, value added and trade.This analysis is based on data provided by the Global Trade Analysis Project (GTAP) of Purdue University. The contribution of agricultural and processed food exports to total supply throughout the Chilean economy is estimated with an Input-Output model of the Chilean economy. This IO model was derived from a new, flexible price, general equilibrium model that was constructed by the authors and is being used for the analysis of selected trade policies in Chile.